Analisis Nilai-nilai Sosial dalam Novel Aku, Kopi, dan Kamera Karya Ainun Nufus - Arviani Arviani; Muhammad Asdar; Andi Nurhabibi Marwil (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The relationship between literary works and society is very inherent, both are interrelated in the reality of life. Literary works are reflections that are realized based on the conditions of society, although not all stories in literary works are exactly the same as social reality, but some literary works emerge from the lives experienced by the author or the people around him. Novel Aku, Kopi, dan Kamera by Ainun Nufus is one of the novels that achieved the title of best seller and has been printed many times because of the high interest in reading from its readers. This study aims to describe the social values ​​in the novel Aku, Kopi, dan Kamera by Ainun Nufus. The analysis of social values ​​is studied using Zubaedi's theory which puts forward social values ​​consisting of compassion, responsibility, and harmony in life. This study uses a qualitative approach that produces descriptive data in the form of written words from the observed characters. The data source comes from the novel Aku, Kopi, dan Kamera by Ainun Nufus published in 2017 by CV. Diandra Primamitra Media with a total of 165 pages. The data collected consisted of words, phrases, clauses, sentences, and paragraphs that refer to social values. The technique used was listening followed by note-taking. After all the data was collected, the next process was data analysis, which was carried out by reducing the data, presenting the data, and then verifying or drawing conclusions. Based on the research results, it can be concluded that the social values ​​found in the novel Aku, Kopi, dan Kamera by Ainun Nufus consist of love, including devotion, kinship, mutual assistance, caring, and loyalty. The second social value is responsibility, including a sense of belonging, empathy, and discipline. The last social value is life harmony, including justice, cooperation, tolerance, and democracy.